The Qur’anic Concept of Human Beings: Ontological, Teleological, and Educational Perspectives - Rifald Rizal (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines the Qur’anic concept of human beings through ontological, teleological, and educational perspectives. Using qualitative library research and a thematic interpretation approach, the study analyzes selected Qur’anic verses related to insān, bashar, al-nās, human creation, dignity, fiṭrah, servitude, vicegerency, and moral responsibility. The analysis is supported by classical and contemporary Qur’anic exegesis and recent studies in Islamic philosophy and education. The findings show that the Qur’an presents human beings as multidimensional creatures whose bodily, intellectual, psychological, moral, social, and spiritual dimensions form an integrated unity. Human existence is directed toward two complementary purposes: serving Allah as ‘abd and fulfilling responsibility on earth as khalīfah. These functions are connected through amānah, which requires the responsible use of knowledge, freedom, authority, and natural resources. The study further demonstrates that this Qur’anic conception provides a philosophical foundation for holistic Islamic education. Islamic education should therefore develop learners’ intellectual competence, spiritual awareness, moral discipline, social responsibility, physical well-being, and ecological consciousness. The study contributes an integrative framework linking Qur’anic anthropology with the aims, curriculum, and practices of Islamic education.